Impact of adalimumab on clinical outcomes, healthcare resource utilization, and sick leave in patients with ankylosing spondylitis: an observational study from five Central and Eastern European countries - Daniela Opris-Belinski; Shandor F Erdes; Simeon Grazio; Ladislav Šenolt; Maja Hojnik; Orsolya Nagy; Diana Marina; Sándor Szántó (Drugs in Context, 2018)
Background: Patients with ankylosing spondylitis (AS) are substantial users of healthcare resources due to chronic and potentially disabling disease. This study assessed the impact of adalimumab on clinical outcomes, healthcare resource utilization, and sick leave in patients with AS in five Central and Eastern Europe (CEE) countries. Methods: This was an observational study in the routine clinical setting. Patients diagnosed with AS and starting treatment with originator adalimumab were followed for 12 months by assessing disease activity (Bath Ankylosing Spondylitis Disease Activity Index [BASDAI] and Ankylosing Spondylitis Disease Activity Score [ASDAS]) and physical function (Bath Ankylosing Spondylitis Functional Index [BASFI]). Data on healthcare resource utilization and sick leave were collected prospectively and compared with historical data before adalimumab initiation, as well as between treatment responders and non-responders defined by BASDAI-50. Results: The total effectiveness population comprised 450 patients with on average long-standing AS, high disease activity, and functional impairment. At 12 months of adalimumab therapy, mean ASDAS and BASFI scores were in the range of low disease activity and normal physical function, respectively. The mean number of hospital admissions, hospital inpatient days, and healthcare provider visits were decreased by 67.9, 83.0, and 46.3%, respectively. The number and length of sick leaves were decreased by 65.6 and 81.4%, respectively. Reductions were higher in treatment responders than non-responders. Conclusion: Originator adalimumab in routine clinical practice in five CEE countries produced clinically meaningful improvements in disease activity and physical function, and it was associated with reductions in healthcare resource utilization and sick leave.